Pore shape and sorption behaviour in mesoporous ordered silica films. Issue 5 (23rd September 2016) - Fritz-Popovski, Gerhard; Morak, Roland; Sharifi, Parvin; Amenitsch, Heinz; Paris, Oskar
Abstract : The shape and sorption behaviour of pores in mesoporous ordered silica films are determined from grazing‐incidence small‐angle X‐ray scattering data. Abstract : Mesoporous silica films templated by pluronic P123 were prepared using spin and dip coating. The ordered cylindrical structure within the films deforms due to shrinkage during calcination. Grazing‐incidence small‐angle X‐ray scattering (GISAXS) measurements reveal that both the unit cell and the cross section of the pores decrease in size, mainly normal to the surface of the substrate, leading to elliptical cross sections of the pores with axis ratios of about 1:2. Water take‐up by the pores upon changing the relative humidity can be monitored quantitatively by the shift in the critical angle of X‐ray reflection as seen by the Yoneda peak.